2012
DOI: 10.3109/13697137.2012.720622
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of porcine placental extract on shoulder stiffness in climacteric women

Abstract: PPE is useful as an oral supplement for shoulder stiffness in climacteric women without HT or in postmenopausal women with HT-resistant, long-term shoulder stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Placental extracts prepared from human or animal placenta have been used as ingredients in medicines, health foods, and cosmetics. Orally administered placental extracts have been reported to be effective for menopausal disorders [ 15 , 16 ] and their symptoms (e.g., knee pain, shoulder stiffness, and wrinkles below the eyes) [ 17 19 ]. Togashi et al reported that an orally administered human placental extract inhibits alcohol-induced hepatic disorder in a mouse model [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Placental extracts prepared from human or animal placenta have been used as ingredients in medicines, health foods, and cosmetics. Orally administered placental extracts have been reported to be effective for menopausal disorders [ 15 , 16 ] and their symptoms (e.g., knee pain, shoulder stiffness, and wrinkles below the eyes) [ 17 19 ]. Togashi et al reported that an orally administered human placental extract inhibits alcohol-induced hepatic disorder in a mouse model [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Porcine placental extract (PPE) have been developed as an alternative source to human placental extracts due to biosafety concerns [ 17 19 , 24 ]. In the current study, we examined PPE-mediated mitigation of oxidative stress, insulin resistance, lipid accumulation, chronic inflammation, and fibrosis in the liver of a diet-induced NASH mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki et al have proposed the recovery system based on physical exercise 143) and/or utilization of foods based on nutrition science [143][144][145][146][147][148][149][150][151][152][153] . than two diploid copies of the salivary amylase genes (AMY1) 155,156) , The mean diploid copy number of AMY1 within 1KJPN data set comprised by the whole genome sequences of 1,070 healthy Japanese individuals was 8.27 156) , which is significantly higher than the number reported in populations with low consumption of starch …”
Section: Pacific Islandsmentioning
confidence: 99%
“…Porcine placental extract (PPE) has been recently developed as an oral supplement for use instead of human placenta extract (HPE) ( Yoshikawa et al ., 2014 ). Previous studies have shown that PPE decreased shoulder stiffness, knee pain, and postmenopausal climacteric symptoms ( Koike et al ., 2012 , 2013a , 2013b ). PPE has been shown to protect skin photoaging through decreased matrix metalloproteinase-2 (MMP-2) and MMP-9 mRNA expression in human skin fibroblasts and in vivo ( Yoshikawa et al ., 2013 ; Hong et al ., 2015 ).…”
Section: Introductionmentioning
confidence: 99%